(Pro)renin receptor contributes to regulation of renal epithelial sodium channel - Quadri, Syed (J Hypertens, 2016)
Recent studies reported increased (Pro)renin receptor (PRR) expression during low-salt intake. We hypothesized that PRR plays a role in regulation of renal epithelial sodium channel (ENaC) through serum and glucocorticoid-inducible kinase isoform 1 (SGK-1)-neural precursor cell expressed, developmentally downregulated 4–2 (Nedd4–2) signaling pathway. Male Sprague–Dawley rats on normal-sodium diet and mouse renal inner medullary collecting duct cells treated with NaCl at 130 mmol/l (normal salt), or 63 mmol/l (low salt) were studied. PRR and α-ENaC expressions were evaluated 1 week after right uninephrectomy and left renal interstitial administration of 5% dextrose, scramble shRNA, or PRR shRNA (n = 6 each treatment). In-vivo PRR shRNA significantly reduced expressions of PRR throughout the kidney and α-ENaC subunits in the renal medulla. In inner medullary collecting duct cells, low salt or angiopoietin II (Ang II) augmented the mRNA and protein expressions of PRR (P < 0.05), SGK-1 (P < 0.05), and α-ENaC (P < 0.05). Low salt or Ang II increased the phosphorylation of Nedd4–2. In cells treated with low salt or Ang II, PRR siRNA significantly downregulated the mRNA and protein expressions of PRR (P < 0.05), SGK-1 (P < 0.05), and α-ENaC expression (P < 0.05). We conclude that PRR contributes to the regulation of α-ENaC via SGK-1-Nedd4–2 signaling pathway.